Analysis of Patient Satisfaction on Disease Polyclinic Services in Pirngadi General Hospital with Fuzzy Service Quality Method - Maisria Yela; Suyanto Suyanto (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2023)
The needs and demands of patients for health services are one of the basic needs. The hospital must know the extent of patient satisfaction with the services provided by the hospital. The purpose of this study was to determine patient expectations for the services received and find out what are the priority improvements to improve the quality of service at Pirngadi Hospital. The method used in this study is the servqual approach combined with fuzzy theory so that the measurement of perceptions and expectations of patients can be measured accurately. The highest gap value is the reliability dimension of -28,17. Thus it can be seen that the reliability dimension is a concern to be able to improve the quality of service especially in ways and attitudes of health workers in serving patients which has the highest gap value of -31,25 of all question variables.